Fiscal policy and gender income inequality: The role of taxes and social spending - Laura Abramovsky; Irene N. Selwaness (Overseas Development Institute (ODI), 2023)
Persistent inequalities between women and men in income, unpaid work, paid work and other dimensions disadvantage women, undermine human rights and damage economic prosperity. Despite the challenges in measuring economic resources at the individual level in a consistent manner across countries, estimates suggest that women are often more likely to be poorer, to live in poorer households or to earn less than men. Systemic differences in unpaid and paid work and earned and unearned income are linked and substantial across countries and regions. Fiscal policies may affect gender inequalities in income and opportunity. This report reviews the evidence on the impact of tax and spending policies on gender income gaps across countries, as well as on work incentives and labour market outcomes for women. The focus is on the role of tax (and social security contributions) and transfers in cash and some transfers in-kind (in the form of education and health services). Given their relevance for women's outcomes after having children, we also survey the evidence on the impact of childcare subsidies (both demand and supply) and paid parental leave. The report concentrates on the impact of fiscal policy on income gaps between genders through redistributing via the tax and benefit system across and within households; and through changing the economic returns to female (formal) employment through tax, transfers and other policies that reduce women's unpaid work burden and hence the opportunity cost of doing paid work.
Keywords: 330; Tax; Public finance; Inequality